Asymmetric Effects of Corruption on FDI: Evidence from Swedish Multinational Firms - Katariina Hakkala; Pehr-Johan Norbäck; Helena Svaleryd (The Research Institute of Industrial Economics (IUI), 2005)
We examine the effect of corruption on foreign direct investments. Our model shows that corruption may have different effects on investments aimed at selling to a local market, in comparison to investments aimed at selling from the corrupt market. Using Swedish firm-level data, we find that affiliate local sales decrease with corruption, while affiliate exports increase. Finally, corruption has a negative effect on the probability that a foreign firm will invest in a country. These results are consistent with theory when bribing reduces production costs and local firms have an advantage in bribing vis à vis foreign firms.
Keywords: D73; F21; F23; 330; FDI; Corruption; Multinational Firm; Korruption; Direktinvestition; Multinationales Unternehmen; Auslandsmarkt; Importwirtschaft; Schweden